Effect of Zingiber officinale Rhizome Powder on Fasting Blood Sugar Levels and HbA1c in Type 2 Diabetes Mellitus Patients: A Meta-Analysis - Novianto, Fajar; Tamtomo, Didik Gunawan; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Diabetes mellitus (DM) type 2 is the most common type of diabetes caused by insulin resistance and relative deficiency of insulin secretion. Several studies have shown inconsistent results regarding the effect of Zingiber officinale powder in patients with type 2 DM. As a result of these inconsistencies, researchers are compelled to prove the effect of Zingiber officinale powder on fasting blood sugar (GDP) and HbA1c levels in type 2 DM patients through a meta-analysis study.Subject and Method: This study is a meta-analysis of a number of randomized controlled trials. The articles were obtained from the PubMed, Science Direct, Springerlink and Google Scholar databases published in 2012-2022. The search articles were carried out by considering the feasibility of the criteria determined using the PICO model. Population: type 2 DM patients, Intervention: Zingiber officinale rhizome powder, Comparison: placebo, Outcome: GDP and HbA1c levels. The keywords used are “Zingiber officinale” OR “Zingiber” OR “Z. officinale” OR “Ginger” AND “Fasting blood glucose” AND “HbA1c” OR “A1c” OR “Glicemic” OR “Glucose” OR “Diabetes Mellitus” OR “type 2 diabetes mellitus” AND “Randomized Controlled Trial”. Article selection with PRISMA flow diagram. Analysis of articles using the Revman 5.3 application.Results: A total of 11 articles were reviewed in this study. Analysis of 11 articles showed that administration of Zingiber officinale rhizome powder could significantly reduce GDP levels in type 2 DM patients (Standardized Mean Difference (SMD)= -0.79; 95% CI= -1.32 to -0.26; p= 0.004). Analysis of 10 articles showed that administration of Zingiber officinale rhizome powder could significantly reduce HbA1c levels (SMD = -0.38; 95% CI= -0.55 to -0.22; p<0.001).Conclusion: Zingiber officinale rhizome powder can significantly reduce GDP and HbA1c levels in type 2 DM patients.Keywords: Zingiber officinale, diabetes mellitus tipe 2, GDP, HbA1cCorrespondence: Fajar Novianto. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir.Sutami No.36, Surakarta, Central Java, Indonesia. Email: dr.fajarnovianto@gmail.com.Indonesian Journal of Medicine (2022), 07(01): 39-50https://doi.org/10.26911/theijmed.2022.07.01.05